A pilot randomized controlled trial of de novo belatacept‐based immunosuppression following anti‐thymocyte globulin induction in lung transplantation. Issue 7 (22nd March 2022) - Huang, Howard J.; Schechtman, Kenneth; Askar, Medhat; Bernadt, Cory; Mittler, Brigitte; Dore, Peter; Witt, Chad; Byers, Derek; Vazquez‐Guillamet, Rodrigo; Halverson, Laura; Nava, Ruben; Puri, Varun; et al.
Abstract: The development of donor‐specific antibodies (DSA) after lung transplantation is common and results in adverse outcomes. In kidney transplantation, Belatacept has been associated with a lower incidence of DSA, but experience with Belatacept in lung transplantation is limited. We conducted a two‐center pilot randomized controlled trial of de novo immunosuppression with Belatacept after lung transplantation to assess the feasibility of conducting a pivotal trial. Twenty‐seven participants were randomized to Control (Tacrolimus, Mycophenolate Mofetil, and prednisone, n  = 14) or Belatacept‐based immunosuppression (Tacrolimus, Belatacept, and prednisone until day 89 followed by Belatacept, Mycophenolate Mofetil, and prednisone, n  = 13). All participants were treated with rabbit anti‐thymocyte globulin for induction immunosuppression. We permanently stopped randomization and treatment with Belatacept after three participants in the Belatacept arm died compared to none in the Control arm. Subsequently, two additional participants in the Belatacept arm died for a total of five deaths compared to none in the Control arm (log rank p  = .016). We did not detect a significant difference in DSA development, acute cellular rejection, or infection between the two groups. We conclude that the investigational regimen used in this study is associated with increased mortality after lung transplantation. Abstract : In this randomized controlled trial, the investigators report increased mortality associated with an investigational, Belatacept‐based immunosuppressive regimen after lung transplantation. Newell and Larsen comment on (Page 1735 )